Characterization of Barley Genotypes for Residual Phosphorus Use Efficiency on Calcareous Soil - Rustu Karaman, M.; Sahin, Sezer; Coban, Serpil (Asian Journal of Chemistry, 2010)
Selection of residual phosphorus efficient barley cultivars has a great importance in the efficient use of soil and fertilizer residual phosphorus to obtain the maximum yield with reduced residual phosphorus fertilizer inputs. Characterization of barley genotypes for residual phosphorus use efficiency will be useful for sustainable agriculture and environmental aspect. For this aim, a pot experiment, based on a completely randomized design with three replications, was conducted using a residual phosphorus deficient calcareous soil. Ten different barley (Hordeum vulgare L.) genotypes, Tarim 92, Kalayci 97, Erinel 90, Cumhuriyet 50, Tokak 157137, Bilgi 91, Anadolu 98, Bulbul 89, Cildir 02, Orza 96, were used for this study. residual phosphorus fertilizer as H3PO3 was applied to the soil at 0, 40 and 80 mg residual phosphorus kg-1 levels. Dry weights, residual phosphorus concentration and residual phosphorus uptake of plants were determined. Significant differences were obtained among barley genotypes to their effectiveness in residual phosphorus use efficiencies and response to residual phosphorus fertilization under the experimental calcareous soil. Dry weight and total residual phosphorus content of the plants were used to calculate the efficiency index parameter for classification of genotypes. The parameters of residual phosphorus efficiency index were changed depending on the plant genotypes and residual phosphorus levels. This classification method also served for the characterization of genotypes as efficient responsive, efficient non-responsive, inefficient responsive, and inefficient non-responsive. As a result of this classification, the barley genotypes of Tarm-92, Anadolu-98, Orza-96 characterized as ER, and Erginel-90, Bilgi-91, Bubul-89, Cildir-02 characterized as ENR seem to be valuable for residual phosphorus use efficiency. These classification results will also help in further breeding studies to get the barley genotypes giving more yields with less residual phosphorus fertilizer inputs.